Teaching Information Literacy and Writing Studies Volume 1, First-Year Composition Courses - Veach, Grace (Purdue University Press, 2018)
This volume, edited by Grace Veach, explores leading approaches to foregrounding information literacy in first-year college writing courses. Chapters describe cross-disciplinary efforts underway across higher education, as well as innovative approaches of both writing professors and librarians in the classroom. This seminal work unpacks the disciplinary implications for information literacy and writing studies as they encounter one another in theory and practice, during a time when "fact" or "truth" is less important than fitting a predetermined message. Topics include: reading and writing through the lens of information literacy, curriculum design, specific writing tasks, transfer, and assessment.